Hematotoxic manifestations and management of green pit viper bites in Thailand - Suthimon Thumtecho (2020)
© 2020 Thumtecho et al. terms.php and incorporate. Introduction: Green pit vipers (GPV) are widely distributed throughout Thailand and are responsible for significant morbidity. The primary objective of this study was to characterize clinical presentations and treatment methods for GPV bites. The secondary objective was to demonstrate the earliest and latest onset of hematotoxicity. Methods: GPV bites reported to the Ramathibodi Poison Center between July 1, 2016, and June 30, 2018, were analyzed. Results: There were 288 GPV cases within the study period. Patients were predominantly male (62.8%), and the median age was 40 years (interquartile range (IQR) 22.8–58). Median time from envenomation to hospital presentation was 1 hour (IQR 0.5–2). Patients were primarily bitten on the finger (27.4%). Most patients reported swelling (90.3%). Necrosis and compartment syndrome occurred in 13 and 9 cases, respectively. Systemic effects occurred in 190 cases (65.9%), with median onset 15 hours (IQR 6–28.3) post-bite. Venous clotting time (VCT) showed the highest percentage of abnormalities. Systemic bleeding occurred in 13 cases (4.5%). Monitoring patients for 24, 48, and 72 hours after bites detected 62.7%, 85.9%, and 96.5% of cases with systemic effects, respectively. In total, 184 patients (62.5%) were treated, sometimes repeatedly, with antivenoms (285 courses, 949 vials). The most common indication was prolonged VCT (144 courses, 50.5%). Recurrent systemic effects after antivenom occurred in 11 cases (6.1% of patients received antivenom). No recurrence presented as systemic bleeding. Adverse reactions to antivenom were reported in 44 courses (15.4% of 285 courses), being anaphylaxis in 19 courses (6.7%). Other treatments included antibiotics (192 cases, 66.7%), surgical intervention (10, 34.7%), and blood components (4, 1.4%). Conclusion: Most GPV bites result in envenomation. The most frequent local effect is mild swelling. Systemic bleeding is uncommon. The current recommendation of a 3-day follow-up can detect up to 96% of patients who may require antivenom. No severe morbidity or mortality is reported. Antivenoms are primarily indicated by prolonged VCT. Side effects of antivenom are minimal.